Sagot :
Bonjour
a^2 - b^2 = (a - b)(a + b)
Factoriser les expressions suivantes :
A=(x-2)^2 - 36
A = (x - 2)^2 - 6^2
A = (x - 2 - 6)(x - 2 + 6)
A = (x - 8)(x + 4)
B=1 - (2x +3)^2
B = 1^2 - (2x + 3)^2
B = (1 - 2x - 3)(1 + 2x + 3)
B = (-2x - 2)(2x + 4)
B = (-2)(x + 1) * 2(x + 2)
B = (-4)(x + 1)(x + 2)
C=(3x - 2)^2 - (x +3)^2
C = (3x - 2 - x - 3)(3x - 2 + x + 3)
C = (2x - 5)(4x + 1)
D=(x +5)^2 - (2x - 4)^2
D = (x + 5 - 2x + 4)(x + 5 + 2x - 4)
D = (-x + 9)(3x + 1)
a^2 - b^2 = (a - b)(a + b)
Factoriser les expressions suivantes :
A=(x-2)^2 - 36
A = (x - 2)^2 - 6^2
A = (x - 2 - 6)(x - 2 + 6)
A = (x - 8)(x + 4)
B=1 - (2x +3)^2
B = 1^2 - (2x + 3)^2
B = (1 - 2x - 3)(1 + 2x + 3)
B = (-2x - 2)(2x + 4)
B = (-2)(x + 1) * 2(x + 2)
B = (-4)(x + 1)(x + 2)
C=(3x - 2)^2 - (x +3)^2
C = (3x - 2 - x - 3)(3x - 2 + x + 3)
C = (2x - 5)(4x + 1)
D=(x +5)^2 - (2x - 4)^2
D = (x + 5 - 2x + 4)(x + 5 + 2x - 4)
D = (-x + 9)(3x + 1)
Bonjour,
Factoriser les expressions suivants :
A= (x-2)² - 36
A= (x-2)² - 6²
A= (x-2-6)(x-2+6)
A= (x-8)(x+4)
B= 1 - (2x +3)²
B= (1-2x-3)(1+2x+3)
B= (-2x-2)((2x+4)
B= -2 * 2 (x+1)(x+2)
B= -4(x+1)(x+2)
C=(3x - 2)² - (x +3)²
C= (3x-2-x-3)(3x-2+x+3)
C= (2x-5)(4x+1)
D=(x +5)²- (2x - 4)²
D= (x+5-2x+4)(x+5+2x-4)
D= (-x+9)(3x+1)
D= - (x-9)(3x+1)